Revision total hip arthroplasty: the femoral side using cemented implants - Holt, Graeme (Springer-Verlag, 2010)
Advances in surgical technique and implant technology have improved the ten-year survival after primary total hip arthroplasty (THA). Despite this, the number of revision procedures has been increasing in recent years, a trend which is predicted to continue into the future. Revision THA is a technically demanding procedure often complicated by a loss of host bone stock which may be compounded by the need to remove primary implants. Both cemented and uncemented implant designs are commonly used in the United Kingdom for primary and revision THA and much controversy still exists as to the ideal method of stem fixation. In this article we discuss revision of the femur using cemented components during revision THA. We focus on three clinical scenarios including femoral cement-in-cement revision where the primary femoral cement-bone interface remains well fixed, femoral cement-in-cement revision for peri-prosthetic femoral fractures, and femoral impaction grafting. We discuss the clinical indications, surgical techniques and clinical outcomes for each of these procedures.